EVALUASI KUALITAS BENIH HASIL INDUKSI HORMONAL MENGGUNAKAN KELENJAR HIPOFISIS DENGAN MENGIMPLEMENTASIKAN CARA PEMBENIHAN IKAN YANG BAIK (CPIB) - farikhah, farikhah; Palupi, Triana Retno; al Mubarok, Raden Muhammad minanur Rohman (Jurnal Perikanan Pantura (JPP), 2025)
This activity evaluates the quality of fish seeds according to SNI standards, focusing on seeds produced via hormonal induction using the pituitary gland during the 2023 and 2024 Fish Seed Technology course practicum. The experiment conducted at the Aquaculture Laboratory of Muhammadiyah University of Gresik by used pearl strain dumbo catfish broodstock averaging ±950g, certified from the Mojokerto Freshwater Aquaculture Installation, East Java. The broodstock received a 1:1 pituitary solution injection, and the latent period was monitored until stripping was feasible. The stripped eggs were fertilized with sperm and hatched in a fiber tank (3 x 1.5 x 0.5 m³) until reaching 30 days post-fertilization (PF). Key observation variables included the latent period, fecundity, seed viability (SR, %), and fish seed quality, analyzed according to the SNI 6484.2: 2014 document and scientific literature. Results from the 2023 and 2024 practicum showed a consistent latent period of approximately 6 hours post-induction and a fecundity of 74,277.8 ± 77,385 grains. After 30 days PF, 7,586 seeds survived, with 36 (0.47%) categorized as shooters. The total length (TL) of the seeds ranged from 16.25 ± 3.46 mm to 19.00 ± 1.64 mm. Color grouping revealed the Pale 3 group had the highest percentage at 78%. No abnormalities were observed, and the seeds demonstrated high responsiveness. Overall, the fish seeds exhibited good quality and uniformity in terms of TL, age, color, and symmetry of paired locomotor organs. The findings indicate a need to clarify uniformity criteria in the SNI document and suggest including the shooter ratio in seed containers, as this relates to the unique characteristics of Clarias sp catfish.